Novel printed microwave structure - Li, Rui. (2009)
A novel printed microwave structure was developed which was able to perform the function of a conventional helix structure. The new structure has the advantages of low fabrication cost, small size and low loss. Further studies on the structure attempts to make it into an electronically tunable phase shifter with the addition of ferroelectric material.